Analysis of Online Identity of Public Figures: A Case Study of Pandawara Group : Analisis Identitas Online Tokoh Publik: Studi Kasus Pandawara Group - Wicaksono, Satrio; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
This study analyzes the formation of the online identity of Pandawara Group, a collective renowned for their social activities in raising awareness about environmental issues. The focus of this research includes strategies for building an online identity, managing the challenges of content collapse, and the authenticity displayed on digital platforms. The analysis shows that Pandawara Group successfully utilizes visual narratives and audience interactions to establish themselves as authentic agents of change. However, they also face challenges such as public pressure, the risk of criticism, and the necessity of maintaining content consistency. This study provides recommendations for enhancing their digital communication strategies to better manage risks while leveraging opportunities in the era of social media. Highlights: Strategic Online Identity – Pandawara Group builds authenticity through visual storytelling and active audience engagement. Challenges of Digital Presence – They navigate public scrutiny, criticism, and the demand for consistent content. Enhancing Digital Strategy – Recommendations focus on risk management and optimizing opportunities in social media. Keywords: Online Identity, Content Collapse, Authenticity, Social Media, Pandawara Group, Social Movement.